BATUQUE CHIANDO NO TERREIRO: A PRESENÇA AFRICANA NA LITERATURA DE LOBIVAR MATOS (Polifonia, 2013)
RESUMO: Neste estudo, analiso alguns poemas do escritor sul-matogrossenseLobivar Matos (1915-1947), com vistas a investigar o entrelugarde onde surge o locus de enunciação do próprio poeta: de Sarobá,um bairro de negros da cidade de Corumbá-MS, a fim de demarcar apresença africana em sua literatura.PALAVRAS-CHAVE: presença africana, entre-lugar, literaturaABSTRACT: In this study, I aim at analyzing a few poems written byLobivar Matos (1915-1947), a poet from the state of Mato Grosso do Sul(MS), Brazil. This study intends to investigate the in-between spacewhere the poet’s own enunciation locus stems from in order to delimitthe African presence in his literature: Sarobá, de afro-Brazilianneighborhood in Corumbá-MS.KEYWORDS: African presence, in-between space, literature